2014
DOI: 10.1002/jmv.23943
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association study of HPV‐associated cervical cancer in Japanese women

Abstract: One of the important factors influencing the development of uterine cervical cancer is human papillomavirus infection in women. Usually, the infecting papillomavirus is eliminated from individuals; however, some retain the virus and this is believed to lead to the development of uterine cervical cancer. It is possible that virus elimination or persistent infection depends on an individual's genetic background. To identify single nucleotide polymorphisms associated with susceptibility to persistent infection or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 20 publications
0
35
0
Order By: Relevance
“…However, of these four cervical cancer susceptibility loci, the Affymetrix Genome-Wide SNP Array 6.0 (Affymetrix) we used in our GWAS did not include three SNPs (rs13117307, rs8067378 and rs4282438). To date, three GWAS regarding cervical cancer have been reported, [9][10][11] but there was no consistent association of SNPs across the different GWAS. 4 Because different SNP microarrays were used in these GWAS, coverage of genetic variants was non-identical between the studies.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…However, of these four cervical cancer susceptibility loci, the Affymetrix Genome-Wide SNP Array 6.0 (Affymetrix) we used in our GWAS did not include three SNPs (rs13117307, rs8067378 and rs4282438). To date, three GWAS regarding cervical cancer have been reported, [9][10][11] but there was no consistent association of SNPs across the different GWAS. 4 Because different SNP microarrays were used in these GWAS, coverage of genetic variants was non-identical between the studies.…”
Section: Discussionmentioning
confidence: 99%
“…[4][5][6][7][8] Recently, three genome-wide association studies (GWAS) have identified susceptibility loci for cervical cancer. [9][10][11] Our previous GWAS in the Japanese population did not identify susceptibility loci for cervical cancer. 11 However, two other GWAS in different populations successfully identified cervical cancer susceptibility loci.…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations